Comparative results of surgical and transcatheter (TAVI) treatment of aortic stenosis in patients over 75 years old - N. L. Bayandin; A. G. Krotovsky; K. N. Vasilyev; A. A. Moiseev; T. V. Setyn (Российский кардиологический журнал)
Aim. To assess the results of transcatheter aortic valve implantation (TAVI) in comparison with open surgery for aortic stenosis in patients over 75 years old. Material and methods. We analyzed the results of 33 operations of aortic valve replacement in patients with aortic stenosis performed in the Moscow Municipal Clinical Hospital No. 15 in the period from June 2012 to September 2017. The first group included 21 TAVI operations. In 15 patients TAVI was performed through the femoral artery, 6  — transthoracic through the cardiac apex. All patients with transcatheter intervention were implanted with SAPIEN valves. In the postoperative period all patients showed a decrease in the systolic pressure gradient on the valve to 9,8±4,06 mm Hg. Aortic valve area after the operation has increased on average from 0,72±0,1 cm2 to 1,9±0,3 cm2. For comparison, a control group of 12 patients who underwent aortic valve replacement under cardiopulmonary bypass was formed. All patients had a high operative risk. Euroscore II 6,3±4,9, STS 5,2±3,4.Results. There were no cases of death in the TAVI group. These patients had the following postoperative complications: 3 patients (13,6%)  — complete atrioventricular block, which required permanent pacemaker implantation; it was a significantly more frequent complication of transcatheter interventions. Less frequently in the postoperative period patients had severe acute cardiovascular failure (p=0,001), acute renal failure (p=0,05), paroxysmal atrial fibrillation (p=0,001). The volume of intraoperative blood loss was significantly less in the TAVI group: 147,6±84,4 ml and 666,7±322,9 ml (p=0,05). Mortality in the surgical group was 33% (4 patients). In the surgical group in 2 cases the cause of death was multiple organ failure, in two cases — acute cardiovascular failure. Patients from this group patients had the following postoperative complications: bleeding requiring a resternotomy — 2 (16,7%), pneumonia — 1 (8,3%), heart failure in the postoperative period, requiring prolonged cardiotonic support — 9 (75%), one patient underwent mechanical hemodynamic support, renal failure requiring renal replacement therapy in one patient.Conclusion. Even though surgical aortic valve replacement is the “gold standard” for treating patients with aortic stenosis, the results of operations in the older age group is not sufficient due to the high frequency of postoperative complications. TAVI, proposed by Cribier A, et al. in 2002, gives better results in patients over 75 age group due to the lower incidence of complications in the postoperative period, less intraoperative blood loss. We suppose that it is an alternative for patients of the older age group and high operative risk.